Evolution analysis of the decoupling state and drivers between economic growth and CO2 emissions in RCEP member countries - Xichun Luo; Honghao Zhao (Energy Strategy Reviews)
With the development of urban cities and their economic growth, the increase of CO2 emissions has become challenging, since the Regional Comprehensive Economic Partnership (RCEP) was officially established. To address this challenge, this study analyzes the historical trends in the RCEP economy and CO2 emissions and determines the decoupling state of each member country using the Tapio decoupling model. Furthermore, this research obtains the driving factors affecting CO2 emissions using the Logarithmic Mean Divisia Index (LMDI) model and analyses the driving forces of each member country to achieve the decoupling process by combining the LMDI and Tapio decoupling models. The results show that (1) Japan is the best decoupling country in terms of the decoupling relationship between economic growth and CO2 emissions, while China has the most stable performance. Overall, developed countries exhibit better decoupling state than developing countries. From the aspect of proportion of decoupling states, the optimal state strong decoupling (SD) and the sub-optimal state weak decoupling (WD) account for 20.95 % and 31.43 %, respectively. The total percentage of these two states exceeds 50 %, which indicates a good decoupling status in the RCEP region. (2) The key drivers of CO2 emission growth are economic and population effects, while the key driver of carbon emission reduction is the energy intensity effect. (3) The energy intensity effect is the main driver to achieve the decoupling process, while the greatest obstacle to the decoupling process is the economic effect. Finally, this study provides policy recommendations for the early realization of the decoupling process of economic growth and CO2 emissions in RCEP member countries.